Robot-assisted PFNA surgery improves clinical outcomes in the treatment of unstable femoral intertrochanteric fractures in elderly patients compared with traditional PFNA surgery - Chaolong Lu; Xiao Wei; Lugen Li; Wenxing Lan; Penghuan Wu; Qingyang Hu; Wenhu Li; Qiang Wu; Yunze Kang; Zhengbo Hu (Scientific Reports)
Abstract To assess the clinical outcomes of robot-assisted proximal femoral nail antirotation (PFNA) surgery in elderly patients with unstable femoral intertrochanteric fractures (UFIFs). 151 patients who underwent UFIF and PFNA surgery between January 2020 and May 2024 were analyzed retrospectively. Of these, 78 patients were treated with traditional PFNA surgery (control group), and 73 patients were treated with robot-assisted PFNA surgery (observation group). The observed indicators included visual analog pain scale (VAS) score, surgery time, PFNA operation time, tip-apex distance (TAD), intraoperative blood loss (IBL), perioperative hidden blood loss (PHBL), postoperative allogeneic blood transfusion rate (PABTR), hospital stay, time to first independent walking with crutches postoperatively, time to independent walking without crutches, and Harris hip function score (HHFS). There were no statistically significant differences in general condition between the two groups before surgery. Surgery time, PFNA operation time, IBL, PHBL, PABTR, TAD, hospital stay, time to first independent walking with crutches postoperatively, time to independent walking without crutches, VAS score, and HHFS were significantly improved in the observation group compared with the control group. Thus, compared with traditional PFNA surgery for UFIF in elderly patients, robot-assisted PFNA yields better outcomes in terms of the quality of PFNA surgery, surgical trauma, conserving clinical blood resources, and patient recovery.